Acute Respiratory Distress Syndrome due to Mycoplasma pneumoniae Misinterpreted as SARS-CoV-2 Infection - Carlos Metz; Torben Rixecker; Sebastian Mang; André Becker; Alexander Maßmann; Sören L. Becker; Cihan Papan; Barbara Gärtner; Frederik Seiler; Guy Danziger; Robert Bals; Philipp M. Lepper (Case Reports in Pulmonology, 2021)
Background. In 2020, a novel coronavirus caused a global pandemic with a clinical picture termed COVID-19, accounting for numerous cases of ARDS. However, there are still other infectious causes of ARDS that should be considered, especially as the majority of these pathogens are specifically treatable. Case Presentation. We present the case of a 36-year-old gentleman who was admitted to the hospital with flu-like symptoms, after completing a half-marathon one week before admission. As infection with SARS-CoV-2 was suspected based on radiologic imaging, the hypoxemic patient was immediately transferred to the ICU, where he developed ARDS. Empiric antimicrobial chemotherapy was initiated, the patient deteriorated further, therapy was changed, and the patient was transferred to a tertiary care ARDS center. As cold agglutinins were present, the hypothesis of an infection with SARS-CoV-2 was then questioned. Bronchoscopic sampling revealed Mycoplasma (M.) pneumoniae. When antimicrobial chemotherapy was adjusted, the patient recovered quickly. Conclusion. Usually, M. pneumoniae causes mild disease. When antimicrobial chemotherapy was adjusted, the patient recovered quickly. The case underlines the importance to adhere to established treatment guidelines, scrutinize treatment modalities, and not to forget other potential causes of severe pneumonia or ARDS.